The future status of hydrocarbons in the global economy with reference to the case of Algeria - Bouamli, Yassine (Journal of Human Sciences, 2020)
When oil was first discovered in 1859, it had few uses. As time progressed, modern economic activity has become increasingly dependent on it. This dependence has become a major area of concern following successive oil crises, and has led scientific community, especially geologists and economists to question the peak-Oil. The aim of this article is, on the one hand, the analysis of the arguments of the "Peakists" as well as those of their opponents, and on the other hand, the analysis of the factors that may determine the future place of hydrocarbons, both in the world economy and the Algerian economy. The article concludes that this place will also be affected by several non-geological factors and not only related to current estimates of the reserves of these resources.